Adhesive film, thermoformed article, and method for producing adhesive film

By adding oligomer diol to the primer layer of the adhesive film, the problem that cracks are easily generated during the thermal bending process or molding of the primer layer are solved, and the moldability of the adhesive film is achieved.

CN119768481APending Publication Date: 2025-04-04MITSUBISHI GAS CHEM CO INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202380061575.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the existing adhesive film is heat bending or molded with a mold with a protruding portion, cracks are easily generated from the primer layer, which affects moldability.

Method used

By combining oligomer diol in the primer layer, the elongation of the primer layer is improved, thereby preventing cracks from occurring in the primer layer during thermal bending processing.

Benefits of technology

The adhesive film has excellent moldability, avoids cracking problems in the primer layer during thermal bending or molding, and improves the overall performance of the adhesive film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768481A_ABST
    Figure CN119768481A_ABST
Patent Text Reader

Abstract

The invention provides an adhesive film with excellent formability, a thermoformed body and a manufacturing method of the adhesive film. The adhesive film according to the present invention comprises a base film containing a polycarbonate, a primer layer provided on at least one surface of the base film, and an adhesive layer provided on the surface of the primer layer on the opposite side from the base film, wherein the primer layer is a layer formed from a primer layer composition containing an oligomer diol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive film, a thermoformed body and a method for producing the adhesive film. Background Art

[0002] At present, as the base film of the adhesive film, it is known that a base film of polyolefins such as polypropylene and polyethylene is used. However, polyolefin sheets have problems in heat resistance. On the other hand, in order to improve heat resistance, polyethylene terephthalate and the like are also considered. However, polyethylene terephthalate needs to be improved from the viewpoints of moisture and heat resistance and formability. For this reason, the use of polycarbonate as the base film of the adhesive film is being studied.

[0003] Specifically, Patent Document 1 discloses an adhesive film as a laminate, which includes: a base film containing polycarbonate, a primer layer laminated on at least one surface of the base film, and an adhesive layer laminated on the surface of the primer layer opposite to the base film.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2020 / 162395 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] The above-mentioned adhesive film is an excellent film. In particular, it is beneficial from the viewpoint of chemical resistance, etc. to provide a primer layer between the substrate film and the adhesive layer. However, it is known that when a primer layer is provided, the formability may sometimes deteriorate depending on the application. Specifically, it is known that cracks may sometimes be generated in the primer layer when hot bending is performed after a heat resistance test or when a mold having a protrusion is used for molding.

[0009] The present invention aims to solve the above-mentioned technical problems, and an object of the present invention is to provide an adhesive film having excellent formability, and methods for producing a thermoformed body and the adhesive film.

[0010] Technical solutions for solving technical problems

[0011] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and have found that the above-mentioned technical problems can be solved by blending an oligomer diol in the primer layer.

[0012] Specifically, the above technical problems can be solved by the following technical solutions.

[0013] <1> An adhesive film comprising:

[0014] A substrate film containing polycarbonate,

[0015] a primer layer provided on at least one surface of the substrate film, and

[0016] an adhesive layer provided on the surface of the primer layer opposite to the substrate film,

[0017] The primer layer is a layer formed of a primer layer composition containing an oligomer diol.

[0018] <2> The adhesive film according to <1>, wherein

[0019] The above-mentioned oligomeric diols include polycarbonate diols.

[0020] <3> The adhesive film according to <1> or <2>, wherein

[0021] The primer layer contains polyfunctional urethane (meth)acrylate.

[0022] <4> The adhesive film according to any one of <1> to <3>, wherein

[0023] The primer layer contains fine particles having an average particle size of 0.1 to 10 μm.

[0024] <5> The adhesive film according to <4>, wherein

[0025] The content of the fine particles is 0.1 to 5 parts by mass based on 100 parts by mass of the primer layer.

[0026] <6> The adhesive film according to <4> or <5>, wherein

[0027] In the primer layer, the average thickness T of the portion where the fine particles do not form protrusions on the surface of the primer layer is 2 The average thickness T of the portion where the convex portions are formed on the surface of the primer layer with respect to the fine particles 1 The ratio (T 2 / T 1 ) is 0.3~0.8.

[0028] <7> The adhesive film according to any one of <1> to <6>, wherein

[0029] The number average molecular weight (Mn) of the oligomer diol is 500 to 5,000.

[0030] <8> The adhesive film according to any one of <1> to <7>, wherein

[0031] The oligomer diol mentioned above contains a chain polycarbonate diol.

[0032] <9> The adhesive film according to <8>, wherein

[0033] The above-mentioned linear polycarbonate diol contains a linear diol unit having 3 to 10 carbon atoms.

[0034] <10> The adhesive film according to <8>, wherein

[0035] The linear polycarbonate diol contains 1,5-pentanediol units and / or 1,6-hexanediol units.

[0036] <11> The adhesive film according to any one of <1> to <10>, wherein

[0037] The adhesive layer contains an acrylic adhesive and / or a polyurethane adhesive.

[0038] <12> The adhesive film according to any one of <1> to <11>, wherein

[0039] The thickness of the primer layer is 0.1 to 5 μm.

[0040] <13> The adhesive film according to any one of <1> to <12>, wherein

[0041] The haze of the adhesive film measured in accordance with JIS K7136 is 3% or less.

[0042] <14> The adhesive film according to any one of <1> to <13>, wherein

[0043] The substrate film has a polycarbonate layer and an acrylic resin layer.

[0044] <15> The adhesive film according to any one of <1> to <14>, wherein

[0045] The glass transition temperature of the polycarbonate contained in the above-mentioned base film measured by differential scanning calorimetry is 100 to 140°C.

[0046] <16> The adhesive film according to any one of <1> to <15>, wherein

[0047] The thickness of the substrate film is 30 to 1000 μm.

[0048] <17> The adhesive film according to <1>, wherein

[0049] The oligomer diol contains polycarbonate diol,

[0050] The primer layer contains a polyfunctional urethane (meth)acrylate.

[0051] The number average molecular weight (Mn) of the above oligomer diol is 500 to 5000,

[0052] The oligomer diol contains a chain polycarbonate diol.

[0053] The above-mentioned linear polycarbonate diol contains 1,5-pentanediol units and / or 1,6-hexanediol units.

[0054] The adhesive layer contains acrylic adhesive and / or polyurethane adhesive.

[0055] The glass transition temperature of the polycarbonate contained in the above-mentioned base film measured by differential scanning calorimetry is 100 to 140°C.

[0056] <18> A thermoformed product, which is a thermoformed product of the adhesive film according to any one of <1> to <17>.

[0057] <19> A method for producing an adhesive film according to any one of <1> to <17>, the method comprising:

[0058] a primer layer forming step of applying a primer layer composition containing an oligomeric diol on the surface of a substrate film containing polycarbonate to form a primer layer, and

[0059] The adhesive layer forming step is to apply an adhesive to the surface of the primer layer opposite to the substrate film to form an adhesive layer.

[0060] Effects of the Invention

[0061] According to the present invention, it is possible to provide an adhesive film having excellent formability, and methods for producing a thermoformed body and an adhesive film. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 It is a schematic cross-sectional view in the thickness direction showing the layer structure of the adhesive film of the present invention.

[0063] Figure 2 It is used to explain the average thickness T of the part where the fine particles form the convex part on the surface of the primer layer. 1 The average thickness T of the part where the fine particles do not form convex portions on the surface of the primer layer 2 Schematic diagram of . DETAILED DESCRIPTION

[0064] A specific embodiment (hereinafter referred to as "this embodiment") will be described in detail below. However, the following this embodiment is only an example for explaining the present invention, and the present invention is not limited to this embodiment.

[0065] In the present specification, the use of "to" means that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0066] In this specification, various physical property values ​​and characteristic values ​​are values ​​at 23°C unless otherwise specified.

[0067] In the present specification, "(meth)acrylic acid" means both acrylic acid and methacrylic acid, or either one of them, and "(meth)acryloyl" means both acryloyl and methacryloyl, or either one of them.

[0068] The term "film" in this specification refers to a generally flat molded body that is thin relative to its length and width, and includes sheets, etc. The term "film" in this specification may be a single layer or a multilayer.

[0069] When the measurement methods and the like described in the standards shown in this specification differ by year, unless otherwise specified, the standards as of January 1, 2022 are used.

[0070] Figure 1 and 2 This is a schematic diagram and its scale may not match the actual situation.

[0071] The adhesive film of the present embodiment is characterized in that it includes: a substrate film containing polycarbonate, a primer layer arranged on at least one surface of the substrate film, and an adhesive layer arranged on the surface of the primer layer opposite to the substrate film, wherein the primer layer is a layer formed by a primer layer composition containing oligomer diol. By having such a structure, an adhesive film with excellent formability can be obtained. The reason is that the adhesive film of the present embodiment includes a substrate containing polycarbonate, a primer layer, an adhesive layer, and an acrylic resin layer as required. When such a film is subjected to hot bending processing or when a mold with a protrusion is used for molding, it is known that cracks sometimes occur in the primer layer. This is speculated to be due to the reason that the primer layer cannot follow the bending processing well. In the present embodiment, it is speculated that by combining oligomer diol in the primer layer, the elongation of the primer layer can be increased, and cracks in the primer layer can be effectively suppressed during hot bending processing.

[0072] Furthermore, when the adhesive film is subjected to a heat resistance test or a moisture and heat resistance test, the adhesive of the adhesive film may be transferred (trans-attached) to the adherend. In the present embodiment, polycarbonate diol is used as the oligomer diol for the primer layer, which can effectively inhibit the above-mentioned trans-attachment. This is presumably due to the interaction between the polycarbonate-containing substrate film and the polycarbonate diol, which improves the adhesion between the primer layer and the substrate film.

[0073] Hereinafter, the details of this embodiment will be described.

[0074] The adhesive film of this embodiment is, for example, Figure 1 As shown in the example, it includes a base film 1 containing polycarbonate, a primer layer 2 provided on at least one surface of the base film 1, and an adhesive layer 3 provided on the surface of the primer layer 2 opposite to the base film 1.

[0075] like Figure 1 As described above, the base film 1 containing polycarbonate is in contact with the primer layer 2, and the primer layer 2 is also in contact with the adhesive layer 3. Usually, the adhesive film is used by being bonded to other members on the adhesive layer 3 side.

[0076] In addition, in this embodiment, there is also a case where the base film 1 is formed of two or more layers, the primer layer 2 is formed of two or more layers, or the adhesive layer 3 is formed of two or more layers. As an example of the base film 1 being formed of two or more layers, the base film 1 having a polycarbonate layer and an acrylic resin layer can be cited. In this case, it is preferred that the polycarbonate layer is in contact with the primer layer 2. In addition, an adhesive film having a structure of base film 1 / primer layer 2 / primer layer 2 / adhesive layer 3 and an adhesive film having a structure of base film 1 / primer layer 2 / adhesive layer 3 / adhesive layer 3 can also be exemplified.

[0077] In this embodiment, a primer layer 2 and an adhesive layer may be provided on both sides of the polycarbonate-containing substrate film 1. For example, an adhesive film may be formed of adhesive layer 3 / primer layer 2 / substrate film 1 / primer layer 2 / adhesive layer 3. In this case, the adhesive layer 3 and primer layer 2 on one side may be the same as or different from the adhesive layer 3 and primer layer 2 on the other side.

[0078] The adhesive film of the present embodiment may have other layers in addition to the above-mentioned polycarbonate-containing substrate film 1, primer layer 2, and adhesive layer 3. Specifically, examples of other layers include functional coating films such as hard coat layers and low-reflection coating films.

[0079] Hereinafter, each layer in this embodiment will be described in detail.

[0080] <Base film containing polycarbonate>

[0081] The base film of the present embodiment contains polycarbonate.

[0082] The type of polycarbonate contained in the substrate film is not particularly limited as long as it contains a -[O-R-OC(=O)]- unit having a carbonate bond in the main chain of the molecule (R is a hydrocarbon group, specifically, an aliphatic group, an aromatic group, or a group containing both an aliphatic group and an aromatic group, and may also be a group having a linear structure or a branched structure), but is preferably an aromatic polycarbonate, more preferably a polycarbonate having a bisphenol skeleton, more preferably a polycarbonate having a structural unit derived from at least one of bisphenol A, bisphenol AP, and bisphenol C, further preferably a polycarbonate having a structural unit derived from at least one of bisphenol A and bisphenol AP, and more preferably a polycarbonate having a structural unit derived from bisphenol A. By using such a polycarbonate, better heat resistance and toughness can be achieved. In the polycarbonate having a bisphenol skeleton, it is preferred that 90 mol% or more of all structural units are structural units having a bisphenol skeleton.

[0083] The polycarbonate used for the substrate film preferably includes a polycarbonate having an end structure shown in formula (1). By having such an end structure, a sheet having excellent hot bending properties and a lower glass transition temperature can be obtained while maintaining the toughness of the material. It should be noted that the polycarbonate having an end structure shown in formula (1) means that at least one of the ends has an end structure shown in formula (1). In this embodiment, preferably more than 50 mol% of the polycarbonate contained in the substrate film has at least one end structure shown in formula (1).

[0084] Formula (1):

[0085]

[0086] (In formula (1), R 1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 2 represents a halogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and n is an integer of 0 to 4. )

[0087] R 1 It is preferably an alkyl group or alkenyl group having 12 or more carbon atoms, and more preferably an alkyl group or alkenyl group having 14 or more carbon atoms. 1 It is preferably an alkyl group or alkenyl group having 22 or less carbon atoms, and more preferably an alkyl group or alkenyl group having 18 or less carbon atoms. 1 An alkyl group is preferred.

[0088] R 2 It is preferably a fluorine atom, a chlorine atom, a methyl group, an ethyl group or a phenyl group, and is preferably a fluorine atom, a chlorine atom or a methyl group.

[0089] n is preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.

[0090] The terminal structure represented by formula (1) can be added to polycarbonate by using a terminal terminator. The details can be referred to the description of paragraphs 0022 to 0030 of Japanese Patent Application Laid-Open No. 2019-2023, and these contents are incorporated into this specification.

[0091] In addition, the viscosity average molecular weight (Mv) of the polycarbonate is preferably 10,000 or more, more preferably 12,000 or more, more preferably 15,000 or more, and further preferably 20,000 or more. By setting it to above the lower limit, there is a tendency that the durability of the substrate film is further improved. The upper limit of the viscosity average molecular weight (Mv) of the polycarbonate is preferably 45,000 or less, more preferably 40,000 or less, and more preferably 34,000 or less. By setting it to below the upper limit, there is a tendency that the molding processability of the substrate film is further improved.

[0092] The viscosity average molecular weight (Mv) refers to the intrinsic viscosity [η] (unit: dL / g) measured at 25°C using an Ubbelohde viscometer using dichloromethane as a solvent. The viscosity average molecular weight is calculated by the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 ×Mv 0.83 Calculated value.

[0093] When two or more polycarbonates are used, the viscosity average molecular weight (Mv) is the viscosity average molecular weight of the mixture (hereinafter, the same applies to various physical properties).

[0094] The glass transition temperature (Tg) of the polycarbonate used in the present embodiment measured by differential scanning calorimetry is preferably 154°C or less, more preferably 152°C or less, more preferably 140°C or less, and further preferably 135°C or less. By being below the above upper limit, there is a tendency for the hot bending formability of the multilayer body to be further improved. In addition, the glass transition temperature (Tg) of the polycarbonate used in the present embodiment is, for example, 100°C or more, and may further be 120°C or more, or 125°C or more. In particular, by making the glass transition temperature of the polycarbonate measured by differential scanning calorimetry be between 100 and 140°C, an adhesive film with excellent bending processability can be obtained.

[0095] The glass transition temperature is measured according to the description of Examples described below. When the polycarbonate is a mixture of two or more polycarbonates, the glass transition temperature is the glass transition temperature of the mixture of polycarbonates.

[0096] As long as other polycarbonates that can be used for the substrate film do not depart from the scope of the present invention, reference can be made to the description of paragraphs 0042 to 0050 of Japanese Patent Application Publication No. 2017-213771 and the description of paragraphs 0015 to 0041 of Japanese Patent Application Publication No. 2018-090677, and these contents are introduced into this specification.

[0097] The substrate film may further contain additives. As additives, at least one selected from a heat stabilizer, an antioxidant, a flame retardant, a flame retardant aid, an ultraviolet absorber, a release agent, and a colorant may be exemplified. In addition, an antistatic agent, a near infrared blocker, a light diffuser, a fluorescent brightener, an antifogging agent, a fluidity improver, a plasticizer, a dispersant, an antibacterial agent, etc. may also be added to the substrate film.

[0098] As antioxidants, phenolic antioxidants, amine antioxidants, phosphorus antioxidants, thioether antioxidants, etc. can be cited. Among them, in the present invention, phosphorus antioxidants and phenolic antioxidants (preferably hindered phenolic antioxidants) are preferred. From the perspective of being able to make the hue of the substrate film excellent, phosphorus antioxidants are particularly preferred. As phosphorus antioxidants, reference can be made to the records of paragraphs 0098 to 0106 of Japanese Patent Gazette No. 2018-178075, the contents of which are introduced into this specification.

[0099] The total amount of the additives in the base film is preferably 0 to 10% by mass, more preferably 0 to 5% by mass.

[0100] Next, the layer structure of the base film will be described.

[0101] The base film may be a single layer or a multilayer.

[0102] When the substrate film is a single layer, it is preferably a polycarbonate single layer film, and the polycarbonate layer is more preferably a layer in which 90% by mass or more of the polycarbonate layer is polycarbonate.

[0103] When the base film is a multi-layer film, it is more preferable to have a polycarbonate layer and an acrylic resin layer.

[0104] The acrylic resin layer preferably contains an acrylic resin such as polymethyl (meth)acrylate resin (polymethyl acrylate and / or polymethyl methacrylate), and more preferably, 90% by mass or more of the acrylic resin layer is an acrylic resin.

[0105] In the present embodiment, the thickness (total thickness) of the substrate film is preferably 30 μm or more, more preferably 100 μm or more, more preferably 150 μm or more, further preferably 200 μm or more, and further preferably 250 μm or more. By being above the lower limit of 30 μm or more, there is a tendency for the lamination processability to be further improved. In addition, the thickness (total thickness) of the substrate film is preferably 1000 μm or less, more preferably 800 μm or less, more preferably 700 μm or less, further preferably 600 μm or less, and further preferably 500 μm or less. By being below the upper limit of 300 μm or less, there is a tendency for the formability to be further improved.

[0106] In addition, the thickness of the polycarbonate layer in the case where the substrate film has a polycarbonate layer and an acrylic resin layer is not particularly limited, but can be, for example, 1 μm or more, preferably 30 μm or more, more preferably 35 μm or more, more preferably 40 μm or more, further preferably 50 μm or more, further preferably 100 μm or more, and further preferably 200 μm or more. In addition, the thickness of the polycarbonate layer is preferably 900 μm or less, more preferably 800 μm or less, can be 700 μm or less, and can also be 600 μm or less.

[0107] In addition, the thickness of the acrylic resin layer in the case where the substrate film has a polycarbonate layer and an acrylic resin layer is, for example, 1 μm or more, preferably 10 μm or more, more preferably 20 μm or more, more preferably 50 μm or more, and more preferably 60 μm or more. By being above the above lower limit, there is a tendency for the hardness to be improved. In addition, the upper limit of the thickness of the acrylic resin layer is not particularly limited, but is preferably 500 μm or less, more preferably 300 μm or less, and more preferably 150 μm or less. By being below the above upper limit, there is a tendency for molding to become easier.

[0108] <Primer layer>

[0109] The adhesive film of the present embodiment includes a primer layer disposed on at least one surface of the substrate film. The primer layer is a layer formed by a primer layer composition containing an oligomer diol. The primer layer composition is a composition used to form a primer layer, and is sometimes also referred to as a primer coating, etc. An oligomer refers to a polymer obtained by polymerizing a monomer to a relatively low degree, preferably a polymer having a number average molecular weight of 5000 or less.

[0110] Examples of the oligomer diol in the present embodiment include polycarbonate diol, polypropylene glycol, polyalkylene glycol such as polytetramethylene glycol, polyester diol, and epoxy-modified polyol. Polycarbonate diol and polytetramethylene glycol are preferred, and polycarbonate diol is more preferred.

[0111] The polycarbonate diol is preferably a chain polycarbonate diol, more preferably containing a chain diol unit having 3 to 10 carbon atoms, and more preferably containing a 1,5-pentanediol unit and / or a 1,6-hexanediol unit. The chain refers to a straight chain or a branched chain, and does not include a cyclic meaning. In addition, the chain diol unit having 3 to 10 carbon atoms refers to a structural unit composed of one or more chain diols having 3 to 10 carbon atoms. By using a chain polycarbonate diol, the primer layer obtained becomes less rigid and the moldability is improved.

[0112] The number average molecular weight of the oligomer diol used in the present embodiment is preferably 500 or more, more preferably 800 or more, more preferably 1200 or more, further preferably 1500 or more, further preferably 1800 or more, and is preferably 5000 or less, more preferably 4000 or less, more preferably 3500 or less, further preferably 3000 or less, further preferably 2500 or less. Within this range, both the moldability and the coating property of the primer layer can be achieved.

[0113] The number average molecular weight is measured according to the description in the Examples described below.

[0114] About the content of oligomer diol in the primer layer composition used in the present embodiment, relative to 100 parts by mass of solid content (components that become primer layer, generally refers to components that do not include solvents in primer layer composition), preferably 10 parts by mass or more, more preferably 20 parts by mass or more, more preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and more preferably 50 parts by mass or more. By being above the above lower limit mass parts, there is a tendency that the elongation of the primer layer increases and the moldability is further improved. In addition, about the content of oligomer diol in the primer layer composition used in the present embodiment, relative to 100 parts by mass of solid content, preferably 90 parts by mass or less, more preferably 85 parts by mass or less, more preferably 80 parts by mass or less, more preferably 75 parts by mass or less, and more preferably 70 parts by mass or less. By being below the above upper limit mass parts, it is possible to maintain drug resistance.

[0115] The primer layer composition of the present embodiment may contain only one type of oligomer diol or two or more types thereof. When containing two or more types thereof, the total amount is preferably within the above range.

[0116] The primer layer preferably contains a polyfunctional urethane (meth) acrylate. In the primer layer, it is generally preferred that 90% by mass or more, preferably 95% by mass or more, and more preferably 98% by mass or more of all components excluding the microparticles are polyfunctional urethane (meth) acrylate. In addition, 100% by mass of the primer layer can be polyfunctional urethane (meth) acrylate.

[0117] As the polyfunctional urethane (meth)acrylate, an ultraviolet curing type is preferred.

[0118] The polyfunctional urethane (meth)acrylate is preferably a 2- to 4-functional urethane (meth)acrylate, more preferably a 2- or 3-functional urethane (meth)acrylate, and still more preferably a 2-functional urethane (meth)acrylate.

[0119] In the primer layer composition, when the primer layer contains a polyfunctional urethane (meth) acrylate, it is preferred that in addition to the oligomeric diol, it also contains a difunctional or higher-functional isocyanate and a (meth) acrylate compound having a hydroxyl group. By having such a structure, a polyfunctional urethane (meth) acrylate can be obtained.

[0120] As the bifunctional or higher-functional isocyanate, bi- to tetrafunctional isocyanates are preferred, bi- or tri-functional isocyanates are more preferred, and bifunctional isocyanates are still more preferred.

[0121] Furthermore, it is also preferable to use a polyisocyanate that is polymerized by condensation of bifunctional or higher-functional isocyanates or by reaction with diol or the like.

[0122] The isocyanate may be an aliphatic isocyanate or an aromatic isocyanate, but an aliphatic isocyanate is preferred. By using an aliphatic isocyanate, an adhesive film having better formability can be obtained.

[0123] The molecular weight of the isocyanate can be appropriately determined depending on the intended use and the like.

[0124] The molecular weight of the isocyanate is preferably 120 or more, more preferably 150 or more, and even more preferably 200 or more, and is preferably 800 or less, and even more preferably 500 or less.

[0125] The molecular weight of the polyisocyanate is preferably 500 or more, more preferably 1000 or more, and is preferably 30000 or less, more preferably 20000 or less.

[0126] The primer layer composition may contain only one isocyanate or two or more isocyanates. When two or more isocyanates are contained, the molecular weight thereof is the sum of the values ​​obtained by multiplying the molecular weights of the respective isocyanates by the mass fractions.

[0127] Specific examples of the isocyanate include hexamethylene diisocyanate, lysine methyl ester diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, isophorone diisocyanate (IPDI), methylenebis(cyclohexane-4,1-diyl) diisocyanate, and ω,ω′-diisocyanate dimethylcyclohexane.

[0128] About the content of isocyanate in the primer layer composition used in the present embodiment, relative to 100 parts by mass of solid content, preferably more than 5 parts by mass, more preferably more than 7 parts by mass, more preferably more than 8 parts by mass, more preferably more than 9 parts by mass, and more preferably more than 10 parts by mass. By more than the above-mentioned lower limit mass parts, there is a tendency that the chemical resistance of the primer layer is further improved. In addition, about the content of isocyanate in the primer layer composition used in the present embodiment, relative to 100 parts by mass of solid content, preferably less than 40 parts by mass, more preferably less than 30 parts by mass, more preferably less than 25 parts by mass, more preferably less than 20 parts by mass, and more preferably less than 18 parts by mass. By less than the above-mentioned upper limit mass parts, there is a tendency that the toughness of the primer layer is further improved.

[0129] When the primer layer composition of the present embodiment contains two or more isocyanates, it is preferred that the total amount thereof be the above-mentioned content.

[0130] Next, the (meth)acrylate compound having a hydroxyl group will be described.

[0131] The (meth)acrylate compound having a hydroxyl group is a compound having one or more (meth)acryloyloxy groups and one or more hydroxyl groups in the molecule, preferably a compound having 1 to 3 (meth)acryloyloxy groups and 1 to 3 hydroxyl groups in the molecule, and more preferably a compound having one (meth)acryloyloxy group and one hydroxyl group in the molecule.

[0132] The molecular weight of the (meth)acrylate compound having a hydroxyl group is preferably 50 or more, more preferably 80 or more, and more preferably 100 or more. When it is above the above lower limit, there is a tendency that the moldability is further improved. In addition, the upper limit of the molecular weight of the (meth)acrylate compound having a hydroxyl group is preferably 1000 or less, more preferably 900 or less, more preferably 800 or less, further preferably 700 or less, and further preferably 650 or less. When it is below the above upper limit, there is a tendency that sticking can be effectively suppressed.

[0133] The primer layer composition may contain only one (meth)acrylate compound having a hydroxyl group, or may contain two or more. When two or more (meth)acrylate compounds having a hydroxyl group are contained, the molecular weight thereof is the sum of the values ​​obtained by multiplying the molecular weight of the (meth)acrylate compound having a hydroxyl group by the mass fraction.

[0134] Examples of the (meth)acrylate compound having a hydroxyl group include pentaerythritol triacrylate (PETA), dipentaerythritol pentaacrylate (DPPA), hydroxypropyl (meth)acrylate (hydroxypropyl acrylate: HPA), 1-(2-hydroxyethyl) 2-[2-[(1-oxo-2-propenyl)oxy]ethyl 1,2-benzenedicarboxylate, and ε-caprolactone 4-mole adduct of 2-hydroxyethyl acrylate.

[0135] About the content of the (meth) acrylate compound with hydroxyl group in the primer layer composition used in the present embodiment, relative to 100 parts by mass of solid content, preferably 5 parts by mass or more, more preferably 10 parts by mass or more, more preferably 12 parts by mass or more, more preferably 15 parts by mass or more, and more preferably 18 parts by mass or more. By being above the above-mentioned lower limit mass parts, there is a tendency that the chemical resistance of the primer layer is further improved. In addition, about the content of the (meth) acrylate compound with hydroxyl group in the primer layer composition used in the present embodiment, relative to 100 parts by mass of solid content, preferably 60 parts by mass or less, more preferably 50 parts by mass or less, more preferably 45 parts by mass or less, more preferably 40 parts by mass or less, and more preferably 35 parts by mass or less. By being below the above-mentioned upper limit mass parts, there is a tendency that the thermoforming property of the film is further improved.

[0136] When the primer layer composition of the present embodiment contains two or more (meth)acrylate compounds having a hydroxyl group, the total amount preferably reaches the above content.

[0137] In addition to the above components, epoxy (meth) acrylate, acrylic (meth) acrylate, antistatic agent, ultraviolet absorber (ultraviolet blocker), near infrared blocker, microparticles represented by silicon dioxide or metal microparticles, etc. may be added to the primer layer or primer layer composition. The total amount of these is preferably 10% by mass or less of the solid content of the primer layer composition.

[0138] Furthermore, the primer layer composition may contain any of a leveling agent and a photopolymerization initiator. In addition, the primer layer composition may contain a solvent.

[0139] By adding a leveling agent to the primer layer composition, the coating surface can be oriented during the drying process, the surface tension of the coating can be uniformed and reduced, floating spots and shrinkage craters can be prevented, and the wettability to the coated object can be improved. As the leveling agent, for example, silicone surfactants, acrylic surfactants, fluorine surfactants, etc. are preferably used.

[0140] In this embodiment, as described above, the primer layer or the primer layer composition may contain fine particles. By containing fine particles, there is a tendency for the anti-blocking property to be further improved.

[0141] The fine particles may be either organic fine particles or inorganic fine particles, and are preferably inorganic fine particles, more preferably silicon dioxide and metal fine particles, and even more preferably silicon dioxide.

[0142] The average particle size of the microparticles is preferably 0.1 μm or more, more preferably 0.5 μm or more, more preferably 1.0 μm or more, further preferably 1.5 μm or more, and further preferably 2.4 μm or more. By being above the above lower limit, there is a tendency to lose tackiness and further improve the anti-adhesion effect. In addition, the average particle size of the microparticles is preferably 10 μm or less, more preferably 8 μm or less, more preferably 6 μm or less, further preferably 4 μm or less, and further preferably 3 μm or less. By being below the above upper limit, the obtained adhesive film can be made thinner.

[0143] The average particle size of the fine particles in the present embodiment is obtained by observing with a scanning electron microscope (SEM), measuring the primary particle size from the SEM image of the fine particles, and taking the average value of 50 primary particle sizes as the average particle size.

[0144] About the content of microparticles, relative to 100 mass parts of the solid component of the primer layer or the primer layer composition, preferably more than 0.1 mass parts, more preferably more than 0.3 mass parts. By more than the above-mentioned lower limit mass parts, there is a tendency to further improve the anti-blocking effect. In addition, the content of microparticles is preferably less than 5 mass parts, more preferably less than 4 mass parts, more preferably less than 3 mass parts, more preferably less than 2 mass parts, and more preferably less than 1 mass part. By below the above-mentioned upper limit mass parts, there is a tendency to further improve the effect of reducing the haze.

[0145] The primer layer or primer layer composition may contain only one type of fine particles or two or more types. When containing two or more types, the total amount is preferably within the above range.

[0146] Regarding the primer layer, in addition to the above, the descriptions in paragraphs 0012 to 0019 and 0029 to 0030 of JP-A-2016-182791 and the descriptions in paragraphs 0051 to 0056 of JP-A-2015-147837 may be referred to, and these contents are incorporated into this specification.

[0147] The thickness of the primer layer is preferably 0.1 μm or more, more preferably 0.5 μm or more. By being above the above lower limit, the substrate film can be effectively inhibited from whitening due to the solvent when the primer layer composition is applied. In addition, the thickness of the primer layer is preferably 5 μm or less, more preferably 4 μm or less, more preferably 3 μm or less, and further preferably 2 μm or less. By being below the above upper limit, cracks can be less likely to occur during hot bending processing.

[0148] As described later, when the fine particles form projections on the surface of the primer layer, the thickness of the primer layer is an average thickness including the height of the projections, and is an average thickness at any 10 locations.

[0149] In the present embodiment, the average thickness T of the portion of the primer layer where the fine particles do not form protrusions on the surface of the primer layer is 200 Å. 2 The average thickness T of the part where the convex part is formed on the surface of the primer layer with respect to the fine particles 1 The ratio (T 2 / T 1 ) is preferably greater than or equal to 0.3, and is preferably less than or equal to 0.8, more preferably less than or equal to 0.7, more preferably less than or equal to 0.6, and further preferably less than or equal to 0.5.

[0150] Here, using Figure 2 The average thickness T of the part where the microparticles form the convex part on the surface of the primer layer is 1 The average thickness T of the part where the fine particles do not form convex portions on the surface of the primer layer 2 Provide explanation. Figure 2 4 is a diagram showing a state where a primer layer 2 is formed on the surface of a base film (not shown), and 4 represents fine particles contained in the primer layer. The average thickness T of the portion where the convex portion is formed on the surface of the primer layer 1 It means, if Figure 2 As shown in the figure, when the particles protrude from the film surface of the primer layer, the length in the thickness direction (height, T 1’ ) is the average value. Therefore, each T 1’ The value of will vary depending on the height of the convex part, and the average value of these will be taken as T 1 In contrast, the average thickness T of the part where the microparticles do not form convex portions on the surface of the primer layer is 2 It means, if Figure 2 As shown, there is no area where protrusions are formed by particles, that is, the thickness of the film surface.

[0151] <Adhesive layer>

[0152] The adhesive layer in the present embodiment is a layer containing an adhesive.

[0153] The type of adhesive layer is not particularly limited, but preferably contains at least one of an acrylic adhesive, a silicone adhesive and a polyurethane adhesive, and more preferably contains an acrylic adhesive and / or a polyurethane adhesive. By using these adhesives, higher adhesion and adhesion to the primer layer can be achieved.

[0154] The adhesive layer may have removable properties. Even if the adhesive layer has removable properties, it can be adhered again even if it is once peeled off from the patch material.

[0155] Acrylic adhesives are adhesives containing acrylic polymers. Specific examples include Finetack (CT-3088, CT-3850, CT-6030, CT-5020, CT-5030), Quickmaster (SPS-900-IV, Quickmaster SPS-1040NT-25) manufactured by DIC Corporation, and Oribain manufactured by ToyoChem Corporation.

[0156] The silicone adhesive is an adhesive containing a silicone-based polymer, and specific examples thereof include polymers produced from KR-3704 (main agent) and CAT-PL-50T (platinum catalyst) manufactured by Shin-Etsu Chemical Co., Ltd., and the like.

[0157] The polyurethane adhesive is an adhesive containing a polyurethane-based polymer, and specific examples thereof include the adhesive Oribain manufactured by ToyoChem Co., Ltd. and DAIKALAC manufactured by Daido Chemical Industry Co., Ltd.

[0158] Acrylic polymers and polyurethane polymers are compounds having a number average molecular weight of 1000 or more, preferably 2000 or more. The upper limit of the number average molecular weight is, for example, 50000 or less. The number average molecular weight is a polystyrene conversion value measured by GPC (gel permeation chromatography).

[0159] As the adhesive layer, in addition to the above, within the scope not departing from the gist of the present invention, the adhesive layer described in paragraphs 0026 to 00053 of Japanese Patent Publication No. 2017-200975, the adhesive layer described in paragraphs 0056 to 0060 of Japanese Patent Publication No. 2013-020130, the adhesive film of International Publication No. 2016 / 158827, the adhesive layer in paragraphs 0031 to 0032 of Japanese Patent Publication No. 2016-182791, and the rubber-based adhesive layer in paragraphs 0057 to 0084 of Japanese Patent Publication No. 2015-147837 can also be used, and these contents are introduced into this specification.

[0160] The thickness of the adhesive layer is not particularly limited, but is preferably 10 μm or more, more preferably 25 μm or more, more preferably 35 μm or more, and can be 40 μm or more. In addition, the thickness of the adhesive layer is preferably 200 μm or less, more preferably 100 μm or less. By being within the above range, more appropriate adhesive properties and adhesive strength can be achieved.

[0161] <Haze of adhesive film>

[0162] The adhesive film of this embodiment preferably has excellent transparency. Specifically, the haze of the adhesive film measured with reference to JIS K7136 is preferably 3% or less, more preferably 2% or less, more preferably 1.5% or less, further preferably 1% or less, further preferably 0.8% or less, and further preferably 0.6% or less. The lower limit of the haze is ideally 0%, but is actually 0.01% or more.

[0163] The haze measured with reference to JIS K7136 is measured as described in the examples described later.

[0164] <Method for producing adhesive film>

[0165] The adhesive film of this embodiment includes: a primer layer forming step of coating a primer layer composition containing oligomer diol on the surface of a substrate film containing polycarbonate to form a primer layer; and an adhesive layer forming step of coating an adhesive on the surface of the primer layer opposite to the substrate film to form an adhesive layer. With such a configuration, an adhesive film with excellent formability can be obtained.

[0166] More specifically, in the manufacture of the adhesive film, first, preferably a substrate film is formed. In the manufacture of the substrate film, the resin composition for the substrate film molding containing polycarbonate is processed into a sheet (film) by a known method. In the present embodiment, it is particularly preferred that the resin composition for the substrate film molding containing polycarbonate without solvent is melted and extruded to form a substrate film. Specifically, it can be formed by extrusion molding and cast molding. As an example of extrusion molding, it can be cited that the pellets, flakes or powder of the resin composition are melted and mixed by an extruder, and then extruded from a T die head, etc., while the semi-molten sheet obtained is pressed with a roller clamp, while it is cooled and solidified to form a sheet. In addition, the polycarbonate film of a commercial product can also be used.

[0167] In addition, when the substrate film of this embodiment has two or more layers, it can also have two or more layers, for example, a multilayer film (a substrate film having a polycarbonate layer and an acrylic resin layer) obtained by co-extrusion molding a composition containing a polycarbonate and a composition containing an acrylic resin.

[0168] Then, preferably in the primer layer forming step, a primer layer composition containing an oligomeric diol is applied and cured to form a primer layer. The primer layer composition is the same as the primer layer composition described in the section of the primer layer of the adhesive film.

[0169] In addition, in the adhesive layer forming step, an adhesive is applied to the surface of the primer layer formed on the opposite side of the substrate film and cured to form the adhesive layer. Of course, when primer layers are provided on both sides of the substrate film, adhesive layers can be provided on the surface of each primer layer. In this case, the primer layers on both sides and the adhesive layers on both sides can be the same or different.

[0170] As a method for curing the primer layer composition and / or the adhesive, a method such as photocuring and heat curing can be adopted.

[0171] <Thermoformed article, adhesive film, and use of thermoformed article>

[0172] The thermoformed body of the present embodiment is a thermoformed body of the adhesive film of the present embodiment.

[0173] The adhesive film or thermoformed body of this embodiment is preferably bonded to other molded bodies on at least a portion of the surface of the resin molded body and on the above-mentioned adhesive layer side. Here, the other molded body is usually a resin molded body. The resin molded body refers to an object molded by a resin, and refers to the adherend to which the adhesive film or thermoformed body of this embodiment is to be bonded. In this embodiment, thermoforming can be performed after the adhesive film and other molded bodies are bonded. The shape of the other molded body is not particularly limited, and it can be a component or a finished product. In addition, its surface can be smooth, or it can be concave and convex or have a complex shape.

[0174] More specifically, there can be mentioned molding into a three-dimensional shape by TOM molding (direct molding on a transparent article), press molding, thermoforming (preliminary molding and lamination), and the like.

[0175] The adhesive film or thermoformed article of this embodiment can be preferably used as an anti-scattering film or surface protection sheet laminated on the surface or back of a three-dimensional transparent article (glass products, displays, touch screens, VR glasses) in multiple layers. More specifically, the adhesive film of this embodiment can be suitably used for display parts of computers, televisions, plasma displays, etc., and surface protection films of polarizing plates used in liquid crystal display devices.

[0176] Example

[0177] The present invention is described in more detail below by giving examples. The materials, usage amounts, ratios, processing contents, processing operations, etc. shown in the following examples can be appropriately changed without departing from the scope of the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.

[0178] When the measuring equipment used in the examples is difficult to obtain due to discontinuation of production or the like, other equipment having equivalent performance may be used for measurement.

[0179] When the amount of each component is expressed simply as "part", it means "part by mass".

[0180] 1. Raw materials

[0181] <Synthesis Example 1 Synthesis of urethane acrylate compound a>

[0182] (1) In a 1 L three-necked flask equipped with a stirrer, a temperature regulator, and a thermometer, 42.06 g of trimethylhexamethylene diisocyanate and 0.10 g of dibutyltin dilaurate were added, heated in an oil bath to an internal temperature of 80 to 90° C., and stirred until completely dissolved.

[0183] (2) 200.0 g of a polyalkylene carbonate diol (Duranol T5652 (Asahi Chemical Industry Co., Ltd.), a linear polycarbonate diol, a carbonate diol containing 1,5-pentanediol units and 1,6-hexanediol units) having a number average molecular weight of 2000 and 141.55 g of propylene glycol monomethyl ether acetate were uniformly mixed and dissolved, and the resulting solution was poured into a dropping funnel with a side tube. The solution in the dropping funnel was added dropwise to the contents of the above-mentioned (2) under a nitrogen atmosphere while stirring and mixing in a manner such that the temperature of the flask contents was maintained at 80 to 90° C., and the mixture was stirred at this temperature for 2 hours.

[0184] (3) After that, the temperature of the contents in the flask was lowered to 60°C, 30.83 g of 1-(2-hydroxyethyl) 2-[2-[(1-oxo-2-propenyl)oxy]ethyl 1,2-benzenedicarboxylate], 57.19 g of 4 mol of ε-caprolactone adduct of 2-hydroxyethyl acrylate, and 0.1 g of 4-methoxyphenol were uniformly mixed and dissolved, and the resulting solution was quickly added from a dropping funnel different from that in (2), and the reaction was carried out for 4 hours in a manner that maintained the temperature of the contents in the flask at 80 to 90°C.

[0185] (4) After 4 hours, a small amount of sample was taken and confirmed by FT-IR at 2300 cm -1 After the isocyanate absorption peak in the vicinity disappeared, the reaction was terminated to obtain a 30% by mass diluted product of propylene glycol monomethyl ether acetate of a urethane acrylate compound.

[0186] In addition, the number average molecular weight of an oligomer diol, such as a polycarbonate diol, is a value calculated based on the hydroxyl value measured with reference to JIS K1577.

[0187] <Synthesis Example 2 Synthesis of urethane acrylate compound b>

[0188] (1) In a 1 L three-necked flask equipped with a stirrer, a temperature regulator, and a thermometer, 42.06 g of trimethylhexamethylene diisocyanate and 0.1 g of dibutyltin dilaurate were added, heated in an oil bath to an internal temperature of 80 to 90° C., and stirred until completely dissolved.

[0189] (2) 200.0 g of a polyalkylene carbonate diol having a number average molecular weight of 2000 (Duranol T5652 (Asahi Chemical)) and 152.84 g of propylene glycol monomethyl ether acetate were uniformly mixed and dissolved, and the resulting solution was poured into a dropping funnel with a side tube. The solution in the dropping funnel was added dropwise to the contents of the above (2) under a nitrogen atmosphere while stirring and mixing in such a manner that the temperature of the flask contents was maintained at 80 to 90° C., and the mixture was stirred at this temperature for 2 hours.

[0190] (3) After that, the temperature of the contents in the flask was lowered to 60°C, 114.38 g of 4 mol of ε-caprolactone adduct of 2-hydroxyethyl acrylate and 0.1 g of 4-methoxyphenol were uniformly mixed and dissolved, and the resulting solution was quickly added from a dropping funnel different from that in (2), and the reaction was carried out for 4 hours in a manner that maintained the temperature of the contents in the flask at 80 to 90°C.

[0191] (4) After 4 hours, a small amount of sample was taken and confirmed by FT-IR at 2300 cm -1 After the isocyanate absorption peak in the vicinity disappeared, the reaction was terminated to obtain a 30% by mass diluted product of propylene glycol monomethyl ether acetate of a urethane acrylate compound.

[0192] <Synthesis Example 3 Synthesis of urethane acrylate compound c>

[0193] (1) In a 1 L three-necked flask equipped with a stirrer, a temperature regulator, and a thermometer, 42.06 g of trimethylhexamethylene diisocyanate and 0.10 g of dibutyltin dilaurate were added, heated in an oil bath to an internal temperature of 80 to 90° C., and stirred until completely dissolved.

[0194] (2) 200.00 g of a polyalkylene carbonate diol having a number average molecular weight of 2000 (Duranol T5652 (Asahi Chemical)) and 130.25 g of propylene glycol monomethyl ether acetate were uniformly mixed and dissolved, and the resulting solution was put into a dropping funnel with a side tube. The solution in the dropping funnel was added dropwise to the contents of the above (2) under a nitrogen atmosphere while stirring and mixing in such a manner that the temperature of the flask contents was maintained at 80 to 90° C., and the mixture was stirred at this temperature for 2 hours.

[0195] (3) After that, the temperature of the contents in the flask was lowered to 60°C, 61.66 g of 1-(2-hydroxyethyl) 2-[2-[(1-oxo-2-propenyl)oxy]ethyl 1,2-benzenedicarboxylate] and 0.1 g of 4-methoxyphenol were uniformly mixed and dissolved, and the resulting liquid was quickly added from a dropping funnel different from that in (2), and the reaction was carried out for 4 hours in a manner that maintained the temperature of the contents in the flask at 80 to 90°C.

[0196] (4) After 4 hours, a small amount of sample was taken and confirmed by FT-IR at 2300 cm -1 After the isocyanate absorption peak in the vicinity disappeared, the reaction was terminated to obtain a 30% by mass diluted product of propylene glycol monomethyl ether acetate of a urethane acrylate compound.

[0197] <Synthesis Example 4 Synthesis of urethane acrylate compound d>

[0198] (1) In a 1 L three-necked flask equipped with a stirrer, a temperature regulator, and a thermometer, 52.48 g of methylenebis(cyclohexane-4,1-diyl)diisocyanate and 0.1 g of dibutyltin dilaurate were added, heated in an oil bath to an internal temperature of 80 to 90° C., and stirred until completely dissolved.

[0199] (2) 200.0 g of polytetramethylene glycol (PTG-2000 (Hodogaya Chemical)) having a number average molecular weight of 2000 and 146.00 g of propylene glycol monomethyl ether acetate were uniformly mixed and dissolved, and the resulting solution was poured into a dropping funnel with a side tube. The solution in the dropping funnel was added dropwise to the contents of the above (2) under a nitrogen atmosphere while stirring and mixing in a manner such that the temperature of the flask contents was maintained at 80 to 90° C., and the mixture was stirred at this temperature for 2 hours.

[0200] (3) After that, the temperature of the contents in the flask was lowered to 60°C, 30.83 g of 1-(2-hydroxyethyl) 2-[2-[(1-oxo-2-propenyl)oxy]ethyl 1,2-benzenedicarboxylate], 57.19 g of 4 mol of ε-caprolactone adduct of 2-hydroxyethyl acrylate, and 0.1 g of 4-methoxyphenol were uniformly mixed and dissolved, and the resulting solution was quickly added from a dropping funnel different from that in (2), and the reaction was carried out for 4 hours in a manner that maintained the temperature of the contents in the flask at 80 to 90°C.

[0201] (4) After 4 hours, a small amount of sample was taken and confirmed by FT-IR at 2300 cm -1 After the isocyanate absorption peak in the vicinity disappeared, the reaction was terminated to obtain a 30% by mass diluted product of propylene glycol monomethyl ether acetate of a urethane acrylate compound.

[0202] <Synthesis Example 5 Synthesis of Comparative Urethane Acrylate Compound e>

[0203] In a 3L three-necked flask, 987 parts of 1-acryloyloxyethyl-2-hydroxyethyl phthalic acid, 1102 parts of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, 1.4 parts of dibutyltin dilaurate, and 1.4 parts of 2,6-tert-butyl-4-methylphenol were added and uniformly mixed. While controlling the temperature at 60°C, 771 parts of isophorone diisocyanate were added. After the addition was completed, nitrogen substitution was performed and the reaction was completed by stirring at 70°C for 15 hours.

[0204] <Synthesis Example 6 Synthesis of Comparative Urethane Acrylate Compound f>

[0205] 1625 parts of hydroxypropyl acrylate, 0.7 parts of dibutyltin dilaurate, and 1.4 parts of 2,6-tert-butyl-4-methylphenol were added to a 3L three-necked flask and mixed evenly. 1175 parts of xylene diisocyanate were added while controlling the temperature at 60°C. After the addition, the mixture was replaced with nitrogen and stirred at 70°C for 15 hours to complete the reaction.

[0206] <Synthesis Example 7 Synthesis of Urethane Acrylate Compound g>

[0207] (1) In a 1 L three-necked flask equipped with a stirrer, a temperature regulator, and a thermometer, 42.06 g of trimethylhexamethylene diisocyanate and 0.07 g of dibutyltin dilaurate were added, heated in an oil bath to an internal temperature of 80 to 90° C., and stirred until completely dissolved.

[0208] (2) 100.0 g of a polycarbonate diol having a number average molecular weight of 900 (Eternacoll UM-90 (3 / 1) (Ube Industries, Ltd.), a polycarbonate diol containing an alicyclic structure, and a carbonate diol containing cyclohexanedimethanol units and 1,6-hexanediol units) and 98.66 g of propylene glycol monomethyl ether acetate were uniformly mixed and dissolved, and the resulting solution was poured into a dropping funnel with a side tube. The solution in the dropping funnel was added dropwise to the contents of the above (2) under a nitrogen atmosphere while stirring and mixing in a manner such that the temperature of the flask contents was maintained at 80 to 90° C., and the mixture was stirred at this temperature for 2 hours.

[0209] (3) After that, the temperature of the contents in the flask was lowered to 60°C, 30.83 g of 1-(2-hydroxyethyl) 2-[2-[(1-oxo-2-propenyl)oxy]ethyl 1,2-benzenedicarboxylate], 57.19 g of 4 mol adduct of ε-caprolactone of 2-hydroxyethyl acrylate, and 0.07 g of 4-methoxyphenol were uniformly mixed and dissolved, and the resulting solution was quickly added from a dropping funnel different from that in (2), and the reaction was carried out for 4 hours in a manner that maintained the temperature of the contents in the flask at 80 to 90°C.

[0210] (4) After 4 hours, a small amount of sample was taken and confirmed by FT-IR at 2300 cm -1 After the isocyanate absorption peak in the vicinity disappeared, the reaction was terminated to obtain a 30% by mass diluted product of propylene glycol monomethyl ether acetate of a urethane acrylate compound.

[0211] <Preparation of Primer Layer Composition A-1>

[0212] 5 mass % of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added to the urethane acrylate compound a obtained in Synthesis Example 1, and the solid content was adjusted to 30 mass % with propylene glycol monomethyl ether as a solvent.

[0213] <Preparation of Primer Layer Composition A-2>

[0214] To the urethane acrylate compound a obtained in the above-mentioned Synthesis Example 1, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass with a solvent of propylene glycol monomethyl ether, and then 0.5% by mass of silica (average particle size: 2.5 μm, SEAHOSTAR KE-P250 manufactured by Nippon Catalyst Co., Ltd.) was added relative to 100% by mass of the solid content for preparation.

[0215] <Preparation of Primer Layer Composition B-1>

[0216] To the urethane acrylate compound b obtained in Synthesis Example 2, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass using propylene glycol monomethyl ether as a solvent.

[0217] <Preparation of Primer Layer Composition B-2>

[0218] To the urethane acrylate compound b obtained in the above-mentioned Synthesis Example 2, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass with a solvent of propylene glycol monomethyl ether, and then 0.5% by mass of silica (average particle size: 2.5 μm, SEAHOSTAR KE-P250 manufactured by Nippon Catalyst Co., Ltd.) was added relative to 100% by mass of the solid content for preparation.

[0219] <Preparation of Primer Layer Composition C-1>

[0220] To the urethane acrylate compound c obtained in Synthesis Example 3, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass using propylene glycol monomethyl ether as a solvent.

[0221] <Preparation of Primer Layer Composition C-2>

[0222] To the urethane acrylate compound c obtained in the above-mentioned Synthesis Example 3, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass with a solvent of propylene glycol monomethyl ether, and then 0.5% by mass of silica (average particle size: 2.5 μm, SEAHOSTAR KE-P250 manufactured by Nippon Catalyst Co., Ltd.) was added relative to 100% by mass of the solid content for preparation.

[0223] <Preparation of primer layer composition D-1>

[0224] To the urethane acrylate compound d obtained in Synthesis Example 4, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass using propylene glycol monomethyl ether as a solvent.

[0225] <Preparation of primer layer composition D-2>

[0226] To the urethane acrylate compound d obtained in the above-mentioned Synthesis Example 4, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30% by mass with a solvent of propylene glycol monomethyl ether, and then 0.5% by mass of silica (average particle size: 2.5 μm, SEAHOSTAR KE-P250 manufactured by Nippon Catalyst Co., Ltd.) was added relative to 100% by mass of the solid content for preparation.

[0227] <Preparation of Primer Layer Composition E-1>

[0228] The comparative urethane acrylate compound e obtained in the above Synthesis Example 5 and the comparative urethane acrylate compound f obtained in the above Synthesis Example 6 were mixed at a ratio of 50 / 50 (mass ratio), 5 mass % of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30 mass % with a solvent of propylene glycol monomethyl ether.

[0229] <Preparation of Primer Layer Composition E-2>

[0230] The comparative urethane acrylate compound e obtained in the above-mentioned Synthesis Example 5 and the comparative urethane acrylate compound f obtained in the above-mentioned Synthesis Example 6 were mixed at a ratio of 50 / 50 (mass ratio), 5 mass% of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the solid content was adjusted to 30 mass% with a solvent of propylene glycol monomethyl ether, and then 0.5 mass% of silica (average particle size: 2.5 μm, SEAHOSTAR KE-P250 manufactured by Nippon Catalyst Co., Ltd.) was added relative to 100 mass% of the solid content for preparation.

[0231] <Preparation of Primer Layer Composition F>

[0232] Hexafunctional urethane acrylate (manufactured by Negami Industry Co., Ltd. under the trade name UN-3320HC) and bifunctional acrylate (2-(2-vinyloxyethoxy)ethyl acrylate, manufactured by Nippon Catalyst Co., Ltd. under the trade name VEEA) were mixed at a ratio of 90 / 10 (mass ratio), 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins BV) was added, and the mixture was adjusted to a solid content of 30% by mass with a solvent of propylene glycol monomethyl ether.

[0233] <Preparation of Primer Layer Composition G-1>

[0234] To the urethane acrylate compound g obtained in Synthesis Example 7, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins B.V.) was added, and the solid content was adjusted to 30% by mass using propylene glycol monomethyl ether as a solvent.

[0235] <Preparation of Primer Layer Composition G-2>

[0236] To the urethane acrylate compound g obtained in the above-mentioned Synthesis Example 7, 5% by mass of a photopolymerization initiator Omnirad 184D (manufactured by IGM Resins B.V.) was added, and the solid content was adjusted to 30% by mass with a solvent of propylene glycol monomethyl ether, and then 0.5% by mass of silica (average particle size: 2.5 μm, SEAHOSTAR KE-P250 manufactured by Nippon Catalyst Co., Ltd.) was added relative to 100% by mass of the solid content for preparation.

[0237] <Adhesive>

[0238] Adhesive a: To 100 parts of a polyurethane adhesive, DAIKALAC 5024 (manufactured by Daido Chemical Industry Co., Ltd.), 0.1 parts of CORONATE HX (manufactured by Tosoh Corporation) as a curing agent was added, and then 50 parts of toluene as a solvent was added.

[0239] Adhesive b: To 100 parts of a polyurethane adhesive, DAIKALAC 5021 (manufactured by Daido Chemical Industry Co., Ltd.), 0.1 parts of CORONATE HX (manufactured by Tosoh Corporation) as a curing agent was added, and then 50 parts of toluene as a solvent was added.

[0240] 2. Examples 1 to 20, Comparative Examples 1 to 6

[0241] <Production of primer multilayer film>

[0242] On a polycarbonate film (FS-2000H manufactured by MGC Filchter Co., Ltd., glass transition temperature 130°C, thickness 300 μm), a primer layer composition of the type shown in Table 1 or Table 2 was applied using a rod coater in such a manner that the dry film thickness became 1 μm, dried at 100°C for 1 minute in a hot air circulation dryer, and cured by irradiation with an ultraviolet irradiation device (accumulated light quantity 300 mJ / cm 2 ) to obtain a primer multilayer film (polycarbonate film / primer layer).

[0243] The dry film thickness is a value obtained by measuring the thickness at any 10 locations and taking the average value thereof (the same shall apply to the thickness hereinafter). In addition, when the primer layer composition contains silicon dioxide (fine particles), the coating is performed in such a manner that the following conditions are achieved: the average thickness T of the portion where the silicon dioxide (fine particles) forms a convex portion on the surface of the primer layer is 1 The average thickness of any five locations where the convex portions were formed was 2.6 μm, and the average thickness T of the locations where the silica (fine particles) did not form convex portions on the surface of the primer layer was 2.6 μm. 2 The average thickness of the film at any five locations where no projections were formed was 1.1 μm.

[0244] It should be noted that the glass transition temperature is a value measured in the following manner.

[0245] <<Measurement of glass transition temperature (Tg)>>

[0246] Take about 10 mg of sample, and perform two cycles of heating and cooling as described below under the DSC (differential scanning calorimetry) measurement conditions, and measure the glass transition temperature during the second cycle of heating. The intersection of the straight line extending from the baseline on the low temperature side to the high temperature side and the tangent line of the inflection point is taken as the starting glass transition temperature, the intersection of the straight line extending from the baseline on the high temperature side to the low temperature side and the tangent line of the inflection point is taken as the ending glass transition temperature, and the midpoint between the starting glass transition temperature and the ending glass transition temperature is taken as the glass transition temperature (Tg, unit: ° C) in the present invention.

[0247] Measurement start temperature: 30°C

[0248] Heating rate: 10℃ / min

[0249] Reaching temperature: 250℃

[0250] Cooling speed: 20℃ / min

[0251] A differential scanning calorimeter (DSC, manufactured by Hitachi High-Technologies Corporation, “DSC7020”) was used as a measuring device.

[0252] <Adhesive film production>

[0253] The adhesives shown in Table 1 or 2 were applied onto a release PET film (manufactured by Chiyoda Gravure, product number: CR-A) to give a dry coating film thickness of 75 μm. The curing conditions were 80° C. for 1 minute and 110° C. for 1 minute.

[0254] The adhesive side of the obtained release PET film with an adhesive was brought into contact with the surface of the primer layer of the primer multilayer film obtained above, and then pressed using a roll laminator, and then cured at room temperature for 1 week to obtain an adhesive film (polycarbonate film / primer layer / adhesive layer / release PET film).

[0255] <Production of a primer multilayer film with an acrylic resin layer>

[0256] First, a multilayer test piece in which a polycarbonate film and an acrylic resin layer (polymethyl methacrylate) were laminated was produced according to the following method.

[0257] The multilayer body was formed using a multilayer extruder having a single screw extruder with a shaft diameter of 32 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die with a width of 650 mm connected to the feed block. DELPET 80HD (polymethyl methacrylate resin, manufactured by Asahi Kasei Corporation) as an acrylic resin was melt-extruded from a single screw extruder with a shaft diameter of 32 mm (barrel temperature of 250° C.), and E-2000N (bisphenol A type polycarbonate resin, manufactured by Mitsubishi Engineering-Plastics Corporation) as a polycarbonate resin was melt-extruded from a single screw extruder with a shaft diameter of 65 mm (barrel temperature of 280° C.), and extruded from a T-die into a sheet through a feed block having two types of two-layer distribution pins connected to the extruder, and cooled while transferring the mirror surface using three mirror-finished rollers set at temperatures of 130° C., 140° C., and 180° C. from the upstream side, and rolled up using a winder, thereby producing a multilayer film. The discharge amount of each extruder and the film take-up speed were adjusted to obtain an acrylic resin / polycarbonate resin multilayer film having a total thickness of 300 μm, with an acrylic resin layer thickness of 60 μm and a polycarbonate resin layer thickness of 240 μm.

[0258] The primer layer composition was applied to the polycarbonate film side of the obtained test piece to a thickness of 1 μm, dried at 100° C. for 1 minute, and then irradiated with an ultraviolet irradiation device at a cumulative light intensity of 300 mJ / cm 2 This was cured to obtain a primer multilayer film with an acrylic resin layer (acrylic resin layer / polycarbonate film / primer layer).

[0259] The following evaluations were performed on the obtained primer multilayer film, adhesive film, and primer multilayer film with an acrylic resin layer.

[0260] <Adhesion of primer multilayer film>

[0261] The primer multilayer film was evaluated for adhesion between the polycarbonate film and the primer layer by the cross cut method according to JIS K5600-5-6. The cut line interval was set to 2 mm, and the evaluation was performed according to the following criteria.

[0262] Good: No peeling is observed on any grid.

[0263] Bad: Partial or complete peeling of the grid is visible.

[0264] The evaluation result is determined by the majority rule, with 5 experts judging it as either good or bad.

[0265] <Haze of primer multilayer film>

[0266] The haze of the primer multilayer film was measured in accordance with JIS K7136.

[0267] Specifically, the haze (unit: %) was measured using a haze meter under the conditions of a D65 light source and a 10° field of view.

[0268] The haze meter used was "HM-150" manufactured by Murakami Color Research Laboratory.

[0269] <Moldability 1 (Moldability of primer multilayer film)>

[0270] The primer multilayer film obtained above was cut into 210 mm × 297 mm × 0.3 mm (thickness). The cut primer multilayer film was preheated at 190° C. for 40 seconds, and on a mold having a deep drawing height of 11 mm and a right-angled protrusion with a size of 30 mm in both the longitudinal and lateral directions, the surface of the polycarbonate film side of the primer multilayer film was arranged in contact with the mold, and the primer multilayer film was press-formed using 3.5 MPa high-pressure air.

[0271] The following evaluation was performed based on whether the radius R of the area where the obtained press-molded body and the right-angled portion of the mold were in contact was within 3 mm, and whether the primer layer on the press-molded body had cracks. In the case where the radius R of the area where the obtained press-molded body and the right-angled portion of the mold were in contact exceeded 3 mm, and / or when cracks appeared in the primer layer, the same test was performed using a mold having a deep drawing height of 7 mm and a right-angled protrusion with a size of 30 mm in both the longitudinal and lateral directions.

[0272] The evaluation is conducted by five experts, who make decisions based on the majority rule.

[0273] A: The radius R of the region where the obtained press-molded body contacts the right-angled portion of the mold is within 3 mm, and no cracks occur in the primer layer, indicating a good condition.

[0274] B: Although A is not satisfied, the radius R of the region where the press-molded body obtained by molding with a metal mold having a deep drawing height of 7 mm contacts the right-angled portion of the mold is within 3 mm, and the primer layer has no cracks, and the condition is good.

[0275] C: Other than A and B above (all molds were used and cracks appeared in the primer layer)

[0276] <Moldability 2 (Moldability of a primer multilayer film with an acrylic resin layer)>

[0277] The primer multilayer film with acrylic resin layer obtained above was cut into 210 mm×297 mm×0.3 mm (thickness). The cut primer multilayer film with acrylic resin layer was preheated at 190°C for 40 seconds, and was arranged on a mold having a deep drawing height of 11 mm and a right-angled protrusion with a size of 30 mm in both the longitudinal and lateral directions, so that the surface of the primer multilayer film with acrylic resin layer on the acrylic resin layer side was in contact with the mold, and the primer multilayer film with acrylic resin layer was press-formed using 3.5 MPa high-pressure air.

[0278] The following evaluation was performed based on whether the radius R of the area where the obtained press-molded body and the right-angled portion of the mold were in contact was within 3 mm, and whether the primer layer on the press-molded body had cracks. In the case where the radius R of the area where the obtained press-molded body and the right-angled portion of the mold were in contact exceeded 3 mm, and / or when cracks appeared in the primer layer, the same test was performed using a mold having a deep drawing height of 7 mm and a right-angled protrusion with a size of 30 mm in both the longitudinal and lateral directions.

[0279] The evaluation was conducted by observation under an optical microscope and by five experts, with the majority decision being made.

[0280] A: The radius R of the region where the obtained press-molded body contacts the right-angled portion of the mold is within 3 mm, and no cracks occur in the primer layer, indicating a good condition.

[0281] B: Although A is not satisfied, the radius R of the region where the press-molded body obtained by molding with a die having a deep drawing height of 7 mm contacts the right-angled portion of the die is within 3 mm, and the primer layer has no cracks, and the condition is good.

[0282] C: Other than A and B above (all metal molds were used, and cracks appeared in the primer layer, etc.)

[0283] <Haze of adhesive film>

[0284] The release sheet of the release PET film was peeled off (the adhesive layer was present on the adhesive film side) and the haze was measured in accordance with JIS K7136.

[0285] Specifically, the haze (unit: %) was measured using a haze meter under the conditions of a D65 light source and a 10° field of view.

[0286] The haze meter used was "HM-150" manufactured by Murakami Color Research Laboratory.

[0287] <Adhesion strength of adhesive film>

[0288] The obtained adhesive film was cut into a size of 25 mm in length and 100 mm in width, and the release sheet of the release PET film was peeled off to expose the adhesive layer. After that, the adhesive film was attached to the glass plate in such a way that the exposed adhesive layer (measurement surface) was in contact with the glass plate, and a 2 kg rubber roller (width: about 50 mm) was reciprocated once to prepare a sample for peel strength measurement. After the sample for peel strength measurement was placed in an environment of 25°C and 50% RH for 24 hours, a tensile test in the 180° direction was performed at a peeling speed of 300 mm / min using a peel tester (manufactured by Kyowa Interface Science Co., Ltd.) in accordance with JIS Z0237, and the peeling force (N / 25mm) between the glass plate and the adhesive film was measured.

[0289] The heat resistance test is to attach the adhesive film to the glass, place it at 180°C for 5 minutes, take it out to room temperature, and perform a tensile test in the 180° direction 2 hours later to measure the peel force (N / 25mm) between the glass plate and the adhesive film. It can be said that the smaller the difference between the initial peel force and the peel force after the heat resistance test, the better.

[0290] In addition, the heat and humidity resistance test is to attach the obtained adhesive film to glass, place it at 85°C and 85% RH for 100 hours, take it out to room temperature, and perform a tensile test in a 180° direction 2 hours later to measure the peeling force (N / 25mm) between the glass plate and the adhesive film. It can be said that the smaller the difference between the initial peeling force and the peeling force after the heat and humidity resistance test, the better.

[0291] <Appearance of adhesive film>

[0292] The appearance of the adhesive film after the heat resistance test and the heat and humidity resistance test was observed and evaluated according to the following criteria: The evaluation was performed by 5 experts and the judgment was made by majority rule.

[0293] Transfer adhesion: When measuring, the adhesive is completely transferred from the adhesive film to the adherend.

[0294] Cohesive failure: A situation where delamination occurs between adhesive layers (not applicable).

[0295] Good: Other than the above, for example, no transfer and cohesive failure occurred.

[0296] [Table 1]

[0297]

[0298] [Table 2]

[0299]

[0300] Explanation of symbols

[0301] 1: substrate film; 2: primer layer; 3: adhesive layer; 4: microparticles.

Claims

1. An adhesive film, characterized in that include: A substrate film containing polycarbonate, a primer layer provided on at least one surface of the substrate film, and An adhesive layer is provided on the surface of the primer layer opposite to the substrate film, The primer layer is a layer formed of a primer layer composition containing an oligomeric diol.

2. The adhesive film according to claim 1, characterized in that: The oligomeric diol comprises a polycarbonate diol.

3. The adhesive film according to claim 1 or 2, characterized in that: The primer layer contains polyfunctional urethane (meth)acrylate.

4. The adhesive film according to any one of claims 1 to 3, characterized in that: The primer layer contains fine particles with an average particle size of 0.1 to 10 μm.

5. The adhesive film according to claim 4, characterized in that: The content of the fine particles is 0.1 to 5 parts by mass based on 100 parts by mass of the primer layer.

6. The adhesive film according to claim 4 or 5, characterized in that: The average thickness T of the portion of the primer layer where the fine particles do not form protrusions on the surface of the primer layer is 2 The average thickness T of the portion where the microparticles form the protrusions on the surface of the primer layer is 1 T 2 / T 1 It is 0.3~0.

8.

7. The adhesive film according to any one of claims 1 to 6, characterized in that: The number average molecular weight Mn of the oligomer diol is 500-5000.

8. The adhesive film according to any one of claims 1 to 7, characterized in that: The oligomer diol contains a chain polycarbonate diol.

9. The adhesive film according to claim 8, characterized in that: The chain polycarbonate diol contains a chain diol unit having 3 to 10 carbon atoms.

10. The adhesive film according to claim 8, characterized in that: The linear polycarbonate diol contains 1,5-pentanediol units and / or 1,6-hexanediol units.

11. The adhesive film according to any one of claims 1 to 10, characterized in that: The adhesive layer contains an acrylic adhesive and / or a polyurethane adhesive.

12. The adhesive film according to any one of claims 1 to 11, characterized in that: The thickness of the primer layer is 0.1 to 5 μm.

13. The adhesive film according to any one of claims 1 to 12, characterized in that: The haze of the adhesive film measured in accordance with JIS K7136 is 3% or less.

14. The adhesive film according to any one of claims 1 to 13, characterized in that: The substrate film has a polycarbonate layer and an acrylic resin layer.

15. The adhesive film according to any one of claims 1 to 14, characterized in that: The glass transition temperature of the polycarbonate contained in the substrate film measured by differential scanning calorimetry is 100 to 140°C.

16. The adhesive film according to any one of claims 1 to 15, characterized in that: The thickness of the substrate film is 30 to 1000 μm.

17. The adhesive film according to claim 1, characterized in that: The oligomeric diol contains polycarbonate diol, The primer layer contains multifunctional urethane (meth)acrylate, The number average molecular weight Mn of the oligomer diol is 500 to 5000, The oligomer diol contains a chain polycarbonate diol, The chain polycarbonate diol contains 1,5-pentanediol units and / or 1,6-hexanediol units. The adhesive layer contains an acrylic adhesive and / or a polyurethane adhesive. The glass transition temperature of the polycarbonate contained in the substrate film measured by differential scanning calorimetry is 100 to 140°C.

18. A thermoformed body, characterized in that: The thermoformed body is a thermoformed body of the adhesive film according to any one of claims 1 to 17.

19. A method for producing an adhesive film, which is the method for producing an adhesive film according to any one of claims 1 to 17, the method comprising: a primer layer forming step of applying a primer layer composition containing an oligomeric diol on the surface of a substrate film containing polycarbonate to form a primer layer, and In the adhesive layer forming step, an adhesive is applied to the surface of the primer layer opposite to the base film to form an adhesive layer.

Citation Information

Patent Citations

  • Room cooling and heating machine

    JP1988220030A

  • Data communication device

    JP1988290030A

  • Hard coat film and touch panel using the same

    JP2013020130A

  • Pressure-sensitive adhesive sheet

    JP2015147837A

  • Support sheet

    JP2016182791A